Viabilitas dan Vigor Bibit Seraiwangi (Andropogon nardus L.) setelah Perlakuan Penyimpanan - Nengsih, Yulistiati; Marpaung, Ridawati; Andriyani, Lizyanti; Septiana, Aisyah (Jurnal Media Pertanian, 2025)
The deterioration process in seeds cannot be prevented. One effort to reduce the rate of deterioration is to optimize storage conditions and the appropriate storage period. Optimal storage conditions and the appropriate storage period can maintain seed quality during storage and growth after storage. The study aimed to obtain data on the rate of seed deterioration and growth of citronella plants after storage. The study was conducted from April to August 2025 in the basic laboratory and experimental garden of the Faculty of Agriculture, Batanghari University. The study used a completely randomized design with one factor. The treatment design was the storage duration (h, days) of citronella seeds as follows: h0 = not stored, h1 = 4, h2 = 8, h3 = 12, and h4 = 16 days. Each treatment was repeated 3 times, resulting in 15 experimental plots. Each experimental plot contained 10 seeds, resulting in 150 citronella plant seeds. Observations during storage were the percentage of fresh seeds and the percentage of growing seeds. Observations after storage were plant height, rate of emergence of tillers, number of tillers, clump circumference, fresh weight of herb, and fresh weight of roots. The observation data were analyzed using analysis of variance. If there was a significant effect, it was continued with Duncan's Advanced Test at α level of 5%. Based on the research and data analysis, it can be concluded that the treatment of the duration of storage of citronella seeds had a significant effect on clump circumference, but had no significant effect on plant height, rate of emergence of tillers, number of tillers, fresh weight of herb and fresh weight of roots. The longer the citronella seeds were stored, the growth rate tended to decrease. This is caused by a decrease in seed viability due to the aging process, dehydration, or physiological damage during storage.